Kohesi Pada Lirik Lagu Album Gajah Karya Tulus sebagai Alternatif Bahan Ajar di Sekolah Menengah Atas - Nur Mei Ningsih; Heru Aditia; Sri Widayati (Edukasi Lingua Sastra, 2022)
The problem discussed in this study is the cohesion contained in the lyrics of the song entitled Gajah album by Tulus. The lyrics of the song will be used as alternative teaching materials in high school. The purpose of this study is to describe the cohesion contained in the lyrics of the album's songs and determine whether or not the album is worthy of being used as an alternative teaching material in high school. The method used is descriptive qualitative. The results of this study found 59 cohesion data on grammatical and lexical aspects which include references, substitutions, ellipsis, conjunctions, repetitions and synonyms. From the aspect of teaching materials, the album's song lyrics have met the criteria so that they are worthy of being used as alternative teaching materials for students in high school.